Electromagnetic Analysis of the EAST 4-Strap ICRF Antenna with HFSS Code. (1st February 2015) - Qin, Chengming; Zhang, Xinjun; Zhao, Yanping; Wan, Baonian; Braun, Franz; Wang, Lei; Yang, Qingxi; Yuan, Shuai; Cheng, Yan
Abstract A new ICRF antenna has been designed in EAST, whose aims are to reduce the parallel RF electric fields E‖ and to investigate the current drive using the fast magnetosonic wave. This antenna consists of four toroidally spaced radiating straps. The electrical characteristics of the new antenna are estimated by using a three-dimensional electromagnetic commercial code. The S-parameters, RF current distribution and electromagnetic field distribution on and near the 4-strap antenna are analyzed, and the RF potentials influenced by antenna phasing and radial position are investigated.